2019
DOI: 10.20435/multi.v24i56.1967
|View full text |Cite
|
Sign up to set email alerts
|

Application of good milking practices: economic impacts and bovine raw milk quality

Abstract: The aim of this study was to evaluate the effects of application of the good milking practices on economic aspects as well as on microbiological and sanitary characteristics of raw milk and bovine mammary gland of animals from Sidrolandia/MS farms. A questionnaire was applied to verify the utilization of good milking practices and milk samples of each property were collected from the expansion tanks to evaluate total bacteria and somatic cell counts as well as milk composition and frauds presence, before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…The average values of SCC decreased (31.4%), but no statistically significant difference (p<0.05) was observed when the results were compared before and after the use of the management tools (Figure 2). Similar results were found by Soares et al (2019), which were different from those observed by Bozo et al (2013), who obtained reduction averages of 74.3% for CCS. The non-significant improvement for SCC is related to the short term of the study, as the response to the implementation of good practices for SCC is not as immediate and significant as for TBC.…”
Section: Tablesupporting
confidence: 65%
See 2 more Smart Citations
“…The average values of SCC decreased (31.4%), but no statistically significant difference (p<0.05) was observed when the results were compared before and after the use of the management tools (Figure 2). Similar results were found by Soares et al (2019), which were different from those observed by Bozo et al (2013), who obtained reduction averages of 74.3% for CCS. The non-significant improvement for SCC is related to the short term of the study, as the response to the implementation of good practices for SCC is not as immediate and significant as for TBC.…”
Section: Tablesupporting
confidence: 65%
“…This fact is related to the non-existence of these products in the market in the State of Acre and the complexity of execution reported by producers. Similarly, Soares et al (2019) reported a difficult standardization of disinfectant dilutions and failure to execute the correct action time.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, este procedimento não é realizado por muitos produtores. Soares et al (2019) em estudo realizado em Mato Grosso do Sul, observaram que este procedimento não era realizado em 50% das propriedades.…”
Section: Caracterização Dos Equipamentos Manejo E Limpeza De Ordenhad...unclassified